2021
DOI: 10.5254/rct.21.79903
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Organic Framework: A Smart Replacement for Conventional Nanofillers for the Enhancement of Mechanical Properties and Thermal Stability of SBR Nanocomposite

Abstract: To the best of our knowledge, for the first time, metal-organic framework (MOF), a porous reticular structure, has been tried as a reinforcing filler for rubber. A MOF synthesized by solvothermal reaction between 2-aminoterephthalic acid and aluminum chloride hexahydrate was characterized and incorporated as reinforcing filler in SBR. A comparative investigation on the properties of the well-dispersed, thermally stable nano-MOF composite (SBR-MOF) was carried out with reference to SBR–nano alumina composite (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…The incorporation of MOFs as reinforcement in SBR via a solvothermal reaction between 2-amino terephthalic acid and aluminum chloride hexahydrate was analyzed [120]. A comparative analysis of the characteristics of a uniformly dispersed and thermally resistant nano-MOF composite (SBR-MOF) was conducted with reference to the SBRnano-alumina composite (SBR-nAl).…”
Section: Metal-organic Framework Based Nanocompositementioning
confidence: 99%
See 1 more Smart Citation
“…The incorporation of MOFs as reinforcement in SBR via a solvothermal reaction between 2-amino terephthalic acid and aluminum chloride hexahydrate was analyzed [120]. A comparative analysis of the characteristics of a uniformly dispersed and thermally resistant nano-MOF composite (SBR-MOF) was conducted with reference to the SBRnano-alumina composite (SBR-nAl).…”
Section: Metal-organic Framework Based Nanocompositementioning
confidence: 99%
“…SBR-MOF has better thermal and dynamic mechanical characteristics than the SBR-nAl composite. The porous MOFs encouraged greater polymer chain entangling at the interface [120].…”
Section: Metal-organic Framework Based Nanocompositementioning
confidence: 99%
“…23 In Jessy Joseph et al' research, NH 2 -MIL-53(Al) was introduced into Styrene-Butadiene Rubber (SBR) as a filler, which enhanced the entanglement of the polymer chains at the interface and improved the thermodynamic and dynamic mechanical properties of rubber materials. 24 Zhiqiang Lei et al explored the in situ growth of ZnO nanoparticles onto MOF-Zn and improved the agglomeration behavior of ZnO nanoparticles and facilitated the dispersion of ZnO in rubber through the interaction between MOF-Zn and ZnO nanoparticles. 25 Xing Tian applied different kinds of ZIF materials in the vulcanization of natural rubber, and speculated that ZIF materials have the synergistic effect of accelerating the vulcanization and improving the mechanical properties of the NR matrix in addition to their role as reinforcing fillers.…”
Section: Introductionmentioning
confidence: 99%
“…Gao et al 19 also reported the improvement of thermal‐oxidative stability of silicone rubber by the addition of ZIF‐67. Joseph and his co‐authors 20 proved NH 2 ‐MIL‐53(Al) as reinforcing filler was favorable for the enhanced entanglement of styrene‐butadiene rubber (SBR) chains at the interface so that the thermal and dynamic mechanical properties of SBR‐MOF were superior to SBR‐Al 2 O 3 composite. Lei et al 21 reported in‐situ growth of ZnO nanoparticles on the surface of MOF‐Zn and mentioned that as prepared MOF‐Zn@ZnO promoted the vulcanization of SBR due to the inhibition of agglomeration of ZnO nanoparticles by MOF‐Zn.…”
Section: Introductionmentioning
confidence: 99%